MEDIATION ROLE OF SERVICE QUALITY TO PURCHASE DECISIONS OF AGRICULTURAL PRODUCTS USING TECHNOLOGY - Yuliana Putri; Nila Pratiwi; Tonny Yuwanda; Rindy Citra Dewi (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2022)
Background : Competition in the increasingly fierce business world makes entrepreneurs look for the right strategy to market their products. Consumer purchasing decisions are obtained from a learning process and a thought process that forms a perception. Method : The method of collecting data is through surveys and distributing questionnaires, with a sample of 96 respondents. The analytical method used is path analysis using smartpls. Result : . The results obtained based on the partial test there is a significant positive effect on product quality on service quality. There is an insignificant positive effect of price on service quality. There is a significant positive effect of Product Quality on Buying Decisions. Conclusion : There is a significant positive effect of Product Quality on Buying Decisions through Service Quality. There is a positive and insignificant effect of price on purchasing decisions through service quality